2018
DOI: 10.1080/10826084.2018.1433212
|View full text |Cite
|
Sign up to set email alerts
|

Food Addiction is Associated with Higher Neuroticism, Lower Conscientiousness, Higher Impulsivity, but Lower Extraversion in Obese Patient Candidates for Bariatric Surgery

Abstract: Prevalence of current food addiction was 16.5%. Patients with (vs. without) food addiction had lower conscientiousness (p = .047), higher neuroticism and lower extraversion (p < 0.001), but there was no difference in terms of agreeableness (p = 0.42) or openness (p = 0.16). They were more frequently single (p = .021) and reported higher alexithymia (p < .001) and higher impulsivity sub-scores (p<.05). Conclusions/Importance: Food addiction shares personality traits with substance-related disorders (regarding n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
24
2
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 15 publications
6
24
2
9
Order By: Relevance
“…Other current findings contradict the assumption that the patients might have under‐report psychopathology. In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Other current findings contradict the assumption that the patients might have under‐report psychopathology. In accordance with our hypothesis, the prevalence of probable eating, anxiety, and major depressive disorders in the present sample was as high as expected based on literature (Baldofski et al, ; Brunault et al, ; Brunault et al, ; Ivezaj et al, ; Koball et al, ; Meule et al, ; Meule et al, ; Miller‐Matero et al, ; Ouellette et al, ). The current results further resemble findings from previous studies in bariatric surgery patients that indicate that those with FA are more likely than those without FA to exhibit eating disorder and anxiety and depressive disorder symptoms (Brunault et al, ; Koball et al, ; Meule et al, ; Miller‐Matero et al, ).…”
Section: Discussionsupporting
confidence: 93%
“…It is well known that individuals with obesity seeking bariatric surgery are often suffering from FA (for review, see Ivezaj, Wiedemann, & Grilo, 2017); however, the reported proportions of YFAS based FA diagnoses in preoperative samples showed wide variation, ranging from 6.7% (Chao et al, 2017) to 58% (Sevincer, Konuk, Bozkurt, & Coskun, 2016). There is also evidence that bariatric surgery candidates with FA are more likely to exhibit symptoms of comorbid mental disorders than those without FA, including eating, anxiety, and depressive disorders (Baldofski et al, 2015;Brunault et al, 2016;Brunault et al, 2018;Ivezaj et al, 2017;Koball et al, 2016;Meule et al, 2017;Meule, Heckel, Jurowich, Vögele, & Kübler, 2014;Miller-Matero et al, 2014;Ouellette et al, 2017).…”
mentioning
confidence: 99%
“…Similar findings were shown in a clinical ED cohort, although negative urgency appeared to be the only independent predictor for FA, while self-directedness and emotion dysregulation predicted negative urgency and were highly related to ED-related symptomatology, but not to food addiction itself [32,33]. In individuals with OBE awaiting bariatric surgery, FA was associated with personality traits such as neuroticism, impulsivity, and alexithymia [34], but also more emotion dysregulation, more harm avoidance, and less self-directedness [35].…”
Section: Introductionmentioning
confidence: 54%
“…Moreover, FA is associated with clinical characteristics that are commonly found with other addictive disorders: depression, anxiety [11], comorbid addictive disorders [15], posttraumatic stress disorders [14] and ADHD [16,17]. People with FA show more insecure attachment styles [18] and higher impulsivity [17,19,20], a classical trait of addictive disorders. In ED samples, FA has been associated with a more severe eating pathology and psychopathology, such as higher negative urgency, higher reward dependence and higher harm avoidance [20,21].…”
Section: Introductionmentioning
confidence: 99%